Actual ambulatory care in patients with type 2 diabetes mellitus in Russian Federation according to open label prospectiveobservational study DIA-CONTROL - Marina Vladimirovna Shestakova (Сахарный диабет)
This review presents a comprehensive analysis of actual ambulatory care in patients with type 2 diabetes mellitus provided in 10 federal subjects withinthe period of 1 year. The analysis is based on results from non-interventional open label prospective observational study DIA-CONTROL, whichincluded 9844 patients with DM type 2. The study was aimed to assess the initial level of glycated hemoglobin and its further dynamics according tomeasurements repeated every 3 months. Composition and efficiency of hypoglycemic therapy were also estimated in these patients.Inclusion visit showed 38.5% of patients to have adequate HbA1c levels (8%, which is quite disturbing and suggests a more careful approach to instruction of healthcarespecialists.